2016
DOI: 10.1515/folmed-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR Assay for Identifi cation and Differentiation of Campylobacter jejuni and Campylobacter coli Isolates

Abstract: The multiplex PCR assay is a fast, accurate method for identifi cation of Campylobacter spp. which makes it quite necessary in the clinical diagnostic practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Bacterial pathogens have been confirmed as the leading cause of acute diarrhea amongst outpatients in China ( Wang et al, 2015 ; Shen et al, 2016 ; Chang et al, 2017 ). Campylobacter infection is considered to be one of the leading causes of bacterial gastroenteritis in the developed countries ( Bresee et al, 2012 ; Wei et al, 2014 ; Kaakoush et al, 2015 ; Kumagai et al, 2015 ; Nohra et al, 2016 ; Pavlova et al, 2016 ). One comparable study reported no Campylobacter infections among diarrheal patients in a developed region neither in children (under 5 years, 0/1422)) nor adults (0/1047) ( Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial pathogens have been confirmed as the leading cause of acute diarrhea amongst outpatients in China ( Wang et al, 2015 ; Shen et al, 2016 ; Chang et al, 2017 ). Campylobacter infection is considered to be one of the leading causes of bacterial gastroenteritis in the developed countries ( Bresee et al, 2012 ; Wei et al, 2014 ; Kaakoush et al, 2015 ; Kumagai et al, 2015 ; Nohra et al, 2016 ; Pavlova et al, 2016 ). One comparable study reported no Campylobacter infections among diarrheal patients in a developed region neither in children (under 5 years, 0/1422)) nor adults (0/1047) ( Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial diarrhea is a serious public health problem worldwide, especially Campylobacter spp. considered as a leading cause (Lynch et al, 2011; Wei et al, 2014; Nohra et al, 2016; Pavlova et al, 2016). In this study, the isolation of Campylobacter is also being the most common pathogen among the tested five enteric bacterial pathogens with the ratio of 12.1% (23/190).…”
Section: Discussionmentioning
confidence: 99%
“…Although the reported incidence of campylobacteriosis remained low in Bulgaria, a research study performed between February 2014 and January 2015 examining patients with diarrheal syndrome reported high detection rate of Campylobacter from their stool samples, in which 43% (40/93) of the samples examined were PCR positive for Campylobacter ( Pavlova et al., 2016 ). Furthermore, a recent study examining the presence of Campylobacter in children with acute diarrhea under five years of age reported a high infection rate, raising concerns regarding Campylobacter infection in paediatric patients.…”
Section: Epidemiologymentioning
confidence: 99%